On the Possibility of a Supranational Collective Bargaining of Labour Relations within the BRICS Countries (The Experience of China, India and South Africa) - Evgenevna Frolova, Evgenia; Mikhailovna Belikova, Ksenia; Vladimirovna Badaeva, Natalia (International Journal of Engineering and Technology, 2018)
The development of transnational corporations (TNC) raises the question of an effective system of organization management, in particular, in countries - members of the BRICS. The results of the study showed the use of a collective labor contract in organizations in India, China, South Africa is not widespread. Regulation of social and labor relations is limited to national features, mentality, traditions. For example, in China workers, due to the prevailing attitude and philosophy, do not seek to use a collective labor contract to regulate the relations with the employer. Based on a number of reasons shown in the article, the authors consider that most probably no major changes related to the regulation of labor relations in these countries will occur in the near future.Â Â